2015
DOI: 10.2514/1.j053719
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Stability Analysis of Subsonic Jets Modified for Low-Frequency Noise Reduction

Abstract: This study performs a spatial stability analysis of several jets that have previously been investigated in terms of their noise radiation. The cases include a round jet and two chevron nozzle jets with varying penetration angle. The instability wave evolution in the near-nozzle region is examined to seek for clues as to how and why the mean flow azimuthal inhomogeneity introduced by chevrons modifies the low-frequency noise component. A biglobal stability analysis is performed to determine the most unstable mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…In particular, the normally three-dimensional PSE problem for serrated jets is simplified to a coupled set of two-dimensional ones. Recently, Uzun et al (2015) revisited the two-dimensional version of the inviscid LST and the three-dimensional version of the inviscid PSE problem for serrated jets. Our formulation here allows significant simplification but is otherwise equivalent, except for viscous effects.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the normally three-dimensional PSE problem for serrated jets is simplified to a coupled set of two-dimensional ones. Recently, Uzun et al (2015) revisited the two-dimensional version of the inviscid LST and the three-dimensional version of the inviscid PSE problem for serrated jets. Our formulation here allows significant simplification but is otherwise equivalent, except for viscous effects.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10]. For simplicity, we only take the frequency St = 0.5 as an example, in which three types of most unstable modes are found at z = 0.5r 0 , and the real parts of eigenfunctions of pressure are plotted in Fig.…”
Section: Multiple Instability Modes Of the Chevron Jetmentioning
confidence: 99%
“…3.2, we have identified that the growth rates and phase speeds of the chevron jet are both lower than that of the round jet as z 2r 0 . It has been argued that the higher growth rate and closer to sonic of phase speed, the higher acoustic radiation efficiency of wavepackets [8,10]. This has been suggested as one reason of the low-frequency noise reduction in chevron jets.…”
Section: Acoustic Efficiency Of Linear Wavepacketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме первичных структур (вихрей Кельвина -Гельмгольца) также обнаруживаются вторичные структуры в виде продольных вихрей с ненулевой осевой завихренностью. На основе результатов анализа линейной устойчивости полей средней скорости в работе [11] сделан вывод о том, что инкременты пространственного роста доминирующих азимутальных мод в шевронных струях оказываются существенно ниже, чем для осесимметричных струй, а пики дисперсионных кривых смещены в область более низких частот.…”
Section: Introductionunclassified